Determinants of Extraocular Muscle Volume in Patients with Graves' Disease. (15th February 2012) - El-Kaissi, Samer; Wall, Jack R.
Abstract : Background . To examine factors contributing to extraocular muscle (EOM) volume enlargement in patients with Graves' hyperthyroidism. Methods . EOM volumes were measured with orbital magnetic resonance imaging (MRI) in 39 patients with recently diagnosed Graves' disease, and compared to EOM volumes of 13 normal volunteers. Thyroid function tests, uptake on thyroid scintigraphy, anti-TSH-receptor antibody positivity and other parameters were then evaluated in patients with EOM enlargement. Results . 31/39 patients had one or more enlarged EOM, of whom only 2 patients had clinical EOM dysfunction. Compared to Graves' disease patients with normal EOM volumes, those with EOM enlargement had significantly higher mean serum TSH (0.020 ± 0.005 versus0.007 ± 0.002 mIU/L;P value 0.012), free-T4 (52.9 ± 3.3 versus41.2 ± 1.7  pmol/L;P value 0.003) and technetium uptake on thyroid scintigraphy (13.51 ± 1.7 % versus8.55 ± 1.6 % ;P value 0.045). There were no differences between the 2 groups in anti-TSH-receptor antibody positivity, the proportion of males, tobacco smokers, or those with active ophthalmopathy. Conclusions . Patients with recently diagnosed Graves' disease and EOM volume enlargement have higher serum TSH and more severe hyperthyroidism than patients with normal EOM volumes, with no difference in anti-TSH-receptor antibody positivity between the two groups.